Employment Changes, the Structure of Adjustment Costs, and Plant Size - Øivind Anti Nilsen; Kjell G. Salvanes; Fabio Schiantarelli (Institute for the Study of Labor (IZA), 2003)
In this paper we analyze the pattern of employment adjustment using a rich panel of Norwegian plants. The data suggest that the frequency of episodes of zero net employment changes is inversely related to plant size. We develop and estimate a simple ?q? model of labor demand, allowing for the presence of fixed, linear and convex components of adjustment costs. The econometric evidence supports the existence of purely fixed components, unrelated to plant size. As a result, the range of inaction is wider for smaller plants. The quadratic components of costs are also important. Finally, in most specifications both fixed and convex costs are higher for employment contractions.
Keywords: C23; D21; E24; 330; adjustment costs; employment demand; size; Arbeitsnachfrage; Anpassungskosten; Betriebsgröße; Beschäftigungseffekt; Schätzung; Norwegen